First, i define the sets of the functions $f:A \rightarrow B,g:A \rightarrow B, h:B \rightarrow C $.

Let $z \in C$, by the definition of the function $(h\circ f)$, $\exists x;$

$z=(h\circ f)(x)\implies z=h(f(x))\implies z=h(g(x)) \implies z=(h\circ g)(x)$

Then $(h\circ f)=(h\circ g)$.

Is my show okay?

  • $\begingroup$ Why start at $z\in C$? Better say, let $x\in A$. Then show that $$(h\circ f)(x)=(h\circ g)(x).$$ $\endgroup$ – Juniven Mar 7 '17 at 1:08
  • $\begingroup$ If f=g , h o f is h o g . $\endgroup$ – Jacob Wakem Mar 7 '17 at 1:47

I think this is just about right, except you should instead show this statement for all $x$. I.e. $\forall x\in A$ $$ (h\circ f)(x)=h(f(x))=h(g(x))=(h\circ g)(x)$$ so, $h\circ f=h\circ g$ as functions. Also, you should be careful: there does not necessarily exist an $x$ such that $(h\circ f)(x)=z$, because we don't know that $h\circ f$ is surjective. Instead, for all $x$, there exists a $z$ such that $z=(h\circ f)(x)$.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.